2017
DOI: 10.1186/s12891-017-1669-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness in the intertrochanteric region may be relevant to hip fracture type

Abstract: Background: This study assessed the differences in femoral geometry and bone mineral density between femoral neck fragility fractures and trochanteric fractures. Methods: One hundred and seventeen patients were divided into femoral neck and trochanteric fracture groups. There were 69 patients with femoral neck fractures, 20 men and 49 women with an average age of 75.1 ± 9.6 years and an average body mass index (BMI) value of 21.6 ± 4.1 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…found that patients with femoral neck fractures usually have more than a threefold greater NSA than patients with trochanteric fractures. However, we did not find a difference in HAL and NSA between the two types of hip fracture, and the same results have been reported by Maeda et al. We presume that the different results reported in these studies originate from differences in race, measurements, and small numbers of subjects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…found that patients with femoral neck fractures usually have more than a threefold greater NSA than patients with trochanteric fractures. However, we did not find a difference in HAL and NSA between the two types of hip fracture, and the same results have been reported by Maeda et al. We presume that the different results reported in these studies originate from differences in race, measurements, and small numbers of subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the cortical bone mainly contributes to bone strength. The strength of the femoral neck will decline by less than 10% if all cancellous bone is removed, and cortical thickness in the intertrochanteric region is very thin. This confirms that cortical bone plays a major role in strengthening the proximal femur, particularly cortical thickness at the IT region.…”
Section: Discussionmentioning
confidence: 72%
“…One challenge for future work in Singapore is to compare hip fracture mortality with mortality in a nonfracture cohort matched by CCI score.Compared with cervical fractures, trochanteric fractures are associated with advanced age and with higher CCI score,24 implying a more fragile group of patients. Hips fracturing at the trochanteric region have been documented to have reduced cortical thickness,25 bone mineral density, and bone mechanical strength 26. These fractures can vary in morphology, ranging from simple fractures to highly comminuted, unstable configurations.…”
mentioning
confidence: 99%
“…It has been presented in multiple studies that cortical thickness reduction may result in osteoporotic fractures. [17,18] Sah et al [19] presented that femurs with small radiographic cortical thickness indices had lower T-scores in DXA tests. They presented that finding a radiographic hip cortical thickness index with a value at or below 0.40 should be an alert for referral to osteoporosis evaluation and might be directly related to fracture.…”
Section: Discussionmentioning
confidence: 99%